Toxic effects of cadmium (Cd++) on metabolism of sunflower (Helianthus annuus L.) seedlings - Zengin, F. Kirbag; Munzuroglu, O. (Taylor & Francis as, 2006)
Effects of cadmium chloride (CdCl2H2O) on the content of chlorophyll (a + b), chlorophyll a/b ratio, proline, protein and abscisic acid in sunflower ( Helianthus annuus L.) seedlings has been investigated. One-week-old seedlings were grown at cadmium concentration of 0.05, 0.07 and 0.09 mM for ten days in Hoagland's solution. Elevated cadmium levels increased the abscisic acid contents in roots, shoots and leaves of seedlings. An increase of proline in the leaves of seedlings exposed to cadmium occurred, as well as a decrease of chlorophyll (a + b) and total protein (p < 0.05 or p < 0.01) contents. Thus cadmium levels at certain critical points negatively affect seedling growth.
Keywords: abscisic acid; chlorophyll (a plus b); proline; total protein